EFEKTIVITAS PENDIDIKAN KESEHATAN UNTUK MENINGKATKAN PENGETAHUAN DAN PERILAKU SKRINING KANKER SERVIKS: LITERATURE REVIEW - Siti Noor Hasanah; Friscila, Ika (LPPM Universitas Sari Mulia, 2022)
Background:Cancer is one of the leading causes of death worldwide. One of the most common cancers among women is cervical cancer. The low level of public knowledge about cervical cancer and its prevention methods is one of the main reasons for the low coverage of cervical cancer screening. Women's reluctance to undergo screening is often due to fear of the results, fear of pain during the examination, and feelings of embarrassment. Objective:The objective of this literature review is to gather and summarize literature related to the effectiveness of health education in improving women's knowledge and behavior regarding cervical cancer screening. Method:This study used electronic bibliographic databases, with systematic searches conducted in PubMed and ScienceDirect from 2009 to 2019. High-quality articles were selected based on inclusion criteria, resulting in 11 articles reviewed out of an initial 843. Results:The review identified two main themes: the effectiveness of health education using the Health Belief Model (HBM) concept, and the effectiveness of tools and media on women's behavior regarding cervical cancer screening. The findings indicate that health education significantly influences the improvement of knowledge, perception, attitudes, and behavior of women in undergoing cervical cancer screening.